A study of anatomical variability of the omohyoid muscle and its clinical relevance (Clinics, 2008)
OBJECTIVE: The omohyoid muscle is a long, thin muscle consisting of superior and inferior bellies and an intermediate tendon, which runs obliquely in the lateral cervical region. The omohyoid is important in neck dissections because it is the surgical landmark for level III and IV lymph node metastases. METHODS: In the present study, the anterior and posterior triangle of the neck was dissected in 35 male cadavers and observed for variations in the omohyoid bilaterally. Observations were focused on variations in number, attachments, and position of omohyoid. RESULTS: Among the 35 cadavers studied, double omohyoid was present in one cadaver, inferior belly originated from the clavicle in three cadavers, superior belly merged with the sternohyoid in two cadavers, and the omohyoid received additional slips from the sternum in one cadaver. Standard attachment and position of the omohyoid was observed in the remaining cadavers. CONCLUSION: Variations of this muscle are important because of its close relation to the large vessels and brachial plexus. Because of the direct adhesion of the intermediate tendon to the anterior wall of the internal jugular vein and its connection with it through a thin lamina of the pretracheal layer of the cervical fascia, the contraction of the omohyoid muscle has a direct effect on the lumen of this vessel.